In Search of Biomarkers for Autism Spectrum Disorder. Issue 11 (15th October 2018) - Del Valle Rubido, Marta; McCracken, James T.; Hollander, Eric; Shic, Frederick; Noeldeke, Jana; Boak, Lauren; Khwaja, Omar; Sadikhov, Shamil; Fontoura, Paulo; Umbricht, Daniel
Abstract : Autism Spectrum Disorder (ASD) lacks validated measures of core social functions across development stages suitable for clinical trials. We assessed the concurrent validity between ASD clinical measures and putative biomarkers of core deficits, and their feasibility of implementation in human studies. Datasets from two adult ASD studies were combined (observational study [ n = 19] and interventional study baseline data [ n = 19]). Potential biomarkers included eye‐tracking, olfaction, and auditory and visual emotion recognition assessed via the Affective Speech Recognition test (ASR) and Reading‐the‐Mind‐in‐the‐Eyes Test (RMET). Current functioning was assessed with intelligence quotient (IQ), adaptive skill testing, and behavioral ratings. Autism severity was determined by the Autism Diagnostic Observation Scale‐2 and Social Communication Interaction Test (SCIT). Exploratory measures showed varying significant associations across ASD severity, adaptive skills, and behavior. Eye tracking endpoints showed little relationship to adaptive ability but correlated with severity and behavior. ASR scores significantly correlated with most adaptive behavior domains, as well as severity. Olfaction predicted visual and auditory emotion recognition. SCIT scores related moderately to multiple severity domains, and was the only measure not related with IQ. RMET accuracy was less related to ASD features. Eye tracking, SCIT, and ASR showed high test–retest reliability. We documented associations of proximal biomarkers of social functioning with multiple ASD dimensions. With the exception of SCIT, most correlations were modest, limiting utility as proxy measures of social communication. Feasibility and reliability were high for eye‐tracking, ASR, and SCIT. Overall, several novel experimental paradigms showed potential as social biomarkers or surrogate markers in ASD. Autism Research 2018, 11: 1567–1579 . © 2018 The Authors. Autism Research published by International Society for Autism Research and Wiley Periodicals, Inc. Lay Summary: More accurate measurements of treatment effects are needed to help the development of new drug treatments for autism spectrum disorders (ASD). This study evaluates the relationship between assessments designed to measure behaviors associated with social communication and cognition in ASD with clinical and diagnostic assessments of symptom severity as well as their implementation. The assessments including eye‐tracking, auditory and visual social stimuli recognition, and olfaction identification showed potential for use in the evaluation of treatments for social difficulties in ASD.